Effects of Foeniculum vulgare essential oil compounds, fenchone and limonene, on experimental wound healing - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
We investigated the wound healing efficacy of the Foeniculum vulgare compounds, fenchone and limonene, using an excisional cutaneous wound model in rats. An excision wound was made on the back of the rat and fenchone and limonene were applied topically to the wounds once daily, separately or together, for 10 days. Tissue sections from the wounds were evaluated for histopathology. The healing potential was assessed by comparison to an untreated control group and an olive oil treated sham group. We scored wound healing based on epidermal regeneration, granulation tissue thickness and angiogenesis. After day 6, wound contraction with limonene was significantly better than for the control group. Ten days after treatment, a significant increase was observed in wound contraction and re-epithelialization in both fenchone and limonene oil treated groups compared to the sham group. Groups treated with fenchone and with fenchone + limonene scored significantly higher than the control group, but the difference was not statistically significant compared to the olive oil treated group. Our findings support the beneficial effects of fenchone and limonene for augmenting wound healing. The anti-inflammatory and antimicrobial activities of fenchone and limonene oil increased collagen synthesis and decreased the number of inflammatory cells during wound healing and may be useful for treating skin wounds.
Keywords: essential oil; fenchone; Foeniculum vulgare; limonene; rats; wound healing; IDENTIFICATION; CANCER; CONSTITUENTS; METABOLITES; ALCOHOL; FRUIT; MILL.; L.